Validation of an improved lattice Boltzmann method for incompressible two-phase flows. (15th October 2018) - Inamuro, Takaji; Echizen, Takuya; Horai, Fuminori
Highlights: The validation of an improved LBM for two-phase flows with large density ratio is presented. A layered Poiseuille flow with a pressure difference between the inlet and the outlet is simulated for density ratio of 1000. A milk crown with density ratio of 800 for various Weber numbers are simulated, and the droplet splashing from a crown sheet is clearly computed. Abstract: In this communication, in order to validate a two-phase lattice Boltzmann method proposed by Inamuro et al. [14] furthermore, we simulate two-phase Poiseuille flows with density ratios of 50 and 1000 and a milk crown with density ratio of 800. In the simulations of two-phase Poiseuille flows, the computed results are compared with the analytical solution in good agreement. In the simulations of a milk crown, the droplet splashing from a crown sheet is clearly computed. Also, the crown radius evolution agrees well with theoretical predictions.